Analytic representation of the distributional finite Hankel transform - O. P. Singh; Ram S. Pathak (International Journal of Mathematics and Mathematical Sciences)
Various representations of finite Hankel transforms of generalized functions are obtained. One of the representations is shown to be the limit of a certain family of regular generalized functions and this limit is interpreted as a process of truncation for the generalized functions (distributions). An inversion theorem for the gereralized finite Hankel transform is established (in the distributional sense) which gives a Fourier-Bessel series representation of generalized functions.